THE SYMBOLIC MEANING OF CUSTOM MOTORCYCLES AS A MEDIUM OF IDENTITY EXPRESSION FOR BUILDERS - Aziiz Assariy; RR Roosita Cindrakasih (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2026)
This study aims to understand the symbolic meaning of custom motorcycles as a medium of identity expression among builders in the Cempaka Baru 10 area. Custom motorcycles not only function as a means of transportation but also serve as a medium for expressing values, character, creativity, and the identities of their owners and builders. This study employed a qualitative approach using a descriptive method. Data were collected through in-depth interviews, observations, and documentation involving custom motorcycle builders actively engaged in the Cempaka Baru 10 area. Data analysis was conducted through data reduction, data presentation, and conclusion drawing, while data validity was ensured through source and technique triangulation. The findings reveal that custom motorcycles are interpreted as representations of personal identity, reflecting the builders' character, life experiences, aesthetic preferences, and personal values. The shape, style, color, and various modification elements of the motorcycles contain symbolic meanings that are used to distinguish builders from others while demonstrating their uniqueness and creativity. Furthermore, custom motorcycles function as a form of symbolic communication, enabling builders to convey messages, status, and self-image to their social environment. Therefore, custom motorcycles serve as a medium of identity expression that carries social, cultural, and personal significance for builders.